Glycosphingolipids of Plasma Membranes of Cultured Cells and an Enveloped Virus (SV5) Grown in These Cells - Klenk, Hans-Dieter (1970)
Glycosphingolipids of rhesus monkey kidney (MK), bovine kidney (MDBK), and two lines of hamster kidney (BHK21-F and Hak) cells have been compared with those of parainfluenza (SV5) virions grow in these cells. There are qualitative and quantitative differences in the neutral glycolipids and gangliosides found in the various cells. Cells with a high neutral glycolipid content (MK and MDBK) contain little or no gangliosides, and those with a relatively high ganglioside content (BHK21-F and HaK) contain little neutral glycolipid. Glycosphingolipids are found predominantly in the plasma membranes. Neutral glycolipids of the host cell membrane are incorporated into the envelope of SV5 virions, but neither gangliosides nor protein-bound neuraminic acid are found in virions. The absence of neuraminic acid from the virion may be due to the action of viral neuraminidase.